GE_GERICHTE P/13509/2021 vom 13. August 2021 - GE Cour de justice (2021)
NE BIS IN IDEM;VIOLATION DE DOMICILE;VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);LÉSION CORPORELLE | CPP.310.leta; CPP.310.letb; CP.122; CP.186; CP.144; CP.139; CP.143bis; CP.179septies